Imagery meaning and content in golf: Effects on performance, anxiety, and confidence - Quinton, M. L.; Cumming, J.; Allsop, J.; Gray, R.; William, S. E. (International Journal of Sport and Exercise Psychology, 2018)
This study examined the effect of imagery content and participant skill level on the interpretation (i.e. image meaning) of a negative image (i.e. a golf putt missing the hole), while also investigating the effect of imagery content and skill level on performance, anxiety, and confidence in a golf putting task. Seventy-nine participants (40 novices, 39 expert golfers; M age = 19.54 years, SD = 1.39) completed a golf putting task in which putting anxiety, confidence, and performance were assessed. Participants were then randomly allocated to one of two imagery scripts; imaging missing the target by 20 cm or imaging missing the target by 40 cm before completing the putting block for a second time. Irrespective of imagery condition, experts perceived the imagery as significantly more unhelpful compared to novices (p < .01). At Block 2, the far miss group had significantly higher cognitive (p < .001) and somatic (p = .013) anxiety intensity than at Block 1 and performed significantly worse (p = .003) than the near miss group. However, there were no differences in the perceived helpfulness of the imagery across the imagery groups. Therefore, imagery perception does not always reflect the outcomes experienced. Image meaning is associated with individual characteristics (e.g. skill level).